Ginseng and its active compounds in ovarian aging: mechanistic basis and translational prospects - Li, Yan-Xin; Zhong, Han-Zhi; Wei, Shao-Bin (Frontiers in Pharmacology, 2026)
Ovarian aging is characterized by follicular depletion and declining oocyte quality, encompassing both physiological age-related decline and pathological forms such as diminished ovarian reserve, premature ovarian insufficiency and premature ovarian failure. These changes are associated with long-term systemic comorbidities across the female life course, particularly in the context of estrogen deficiency. Ginseng as a botanical drug (Panax ginseng C.A.Mey.) and its active compounds, including ginsenosides Rg1, Rb1 and Rg3, the gut–derived metabolite Compound K and ginseng polysaccharides, have emerged as multitarget candidates for delaying ovarian aging-associated functional decline and supporting reproductive health. This review integrates preclinical evidence on how ginseng-related compounds attenuate oxidative stress, preserve mitochondrial function, support energy metabolism and modulate ovarian inflammaging and the senescence-associated secretory phenotype. They also rebalance apoptosis and autophagy, thereby supporting granulosa cell survival and follicle development. We summarize their regulatory effects on hypothalamic–pituitary–ovarian axis activity and on ovarian hormone receptor expression, which may help preserve ovarian endocrine function during aging. Across mechanistic domains, the most consistent ovary-relevant evidence converges on redox control and mitochondrial integrity and function, together with dampening of NF-κB and NLRP3-linked inflammatory signaling and SASP-associated features, whereas evidence for direct hypothalamic–pituitary modulation and for durable multisystem outcome modification remains more exploratory. Preclinical studies indicate that ginseng-related compounds can influence skeletal, cardiovascular, hepatic, metabolic and neurocognitive phenotypes that accompany estrogen deficiency. However, the evidence base remains heterogeneous and largely preclinical, and causal links to long-term functional reproductive outcomes are still limited. Interpretation of the existing literature is hampered by differences in botanical sources, processing methods, formulations, dosing regimens, treatment duration and routes of administration, which complicate evaluation of in vivo exposure and pharmacodynamic response, particularly for orally administered ginsenosides that undergo microbiota-mediated biotransformation and show inter-individual pharmacokinetic variability in some studies, with consequent uncertainty in dose relevance and exposure consistency across populations. Further progress toward clinical application may be facilitated by traceable and chemically defined ginseng preparations, exposure-guided oral dosing and rigorously designed clinical trials that better define efficacy, safety, plausible drug–drug interaction considerations and long-term reproductive and systemic outcomes with stage-stratified designs and prioritized functional outcome measures.